Penerapan Relationship Marketing dalam Membangun Hubungan Kemitraan antara Nasabah dan Bank Syari'ah - Zahara, Zakiyah (Universitas Brawijaya, Indonesia, 2011)
The development of Syari'ah banking highly depends on all the parties and indirectly involved in its operation. Therefore, sound cooperation of the parties involved is crucial for the development and sustainability of the bank. Service quality closely corelates with the satisfaction and trust of clients. From trust and satisfaction expected can improve commitment and loyalty of client's. This study aims at determining the influence of: 1. Service quality of Syari'ah bank on its client's satisfaction and trust; 2. Clients satisfaction on their trust, commitment and loyalty to the bank; 3. Client's trust on their commitment and loyalty to the bank, and client's commitment on their loyalty to the bank. The population comprise client's, age over 17 years, saving at the Syari'ah bank. The judgment sampling method is used. The 340 respondents used are the client's registered at the Syari'ah bank and Syari'ah business units in Makassar. The exogen variable is the service quality while the endogen variables are satisfaction, trust, commitment and loyalty. The analysis model used is the Structural Equation Modelling (SEM). The study results reveal that: 1. Client's loyalty can be improved by satisfying service quality followed by the client's commitment itself; 2. Good service quality which is not followed by sound trust, would be unable to establish high loyalty. Trust is the key to the establishment of commitment and loyalty. The honesty of the bank in operating the Syari'ah principles is highly considered by the client's. Trusts and commitment form the basis in building a sound long-term relationship between the client's and the bank.